SOCIAL WELFARE AND POPULATION MOBILITY (MOVEMENT) ANALYSIS IN BANTEN PROVINCE - Riny Handayani (Adisam Publisher, 2024)
The aspect of population mobility in Banten Province is one of the demographic parameters that can describe the success of development, which is why writing related to mapping population mobility is important considering the very dynamic changes in demographic parameters in Banten Province. Population mobility used in this research is included in the category of permanent population mobility or can also be interpreted as migration (population movement). The research method used is quantitative with spatial descriptive analysis techniques. The elaboration stages include data collection, data processing, determining variables and overlaying digital maps. The unit of analysis in this research is the district/city where there are 4 districts and 4 cities. Mapping population mobility in Banten Province is to create a description of the data that has been obtained and display it in simple statistical form so that the public can more easily get an idea of the situation of population mobility in Banten Province. The mobility indicators studied are Incoming Migration, Outgoing Migration, Net Migration, Risen Migration, and the Percentage of Migrant Population. There are significant differences regarding the incidence of population mobility in Banten Province between North and South Banten. Greater Tangerang (Tangerang City, South Tangerang City and Tangerang Regency) is an area with a dominant composition of migrant residents. Regional status is also recorded to influence the incidence of population mobility, where the status of city areas is areas with high incidences of Incoming Migration compared to areas with district status. The policy that must be prepared regarding population mobility is facilitating the preparation of regional facilities and infrastructure related to the flow of movement and population movement, the pattern of which is increasing every year.